Aire Marine Protégée, intérêt général environnemental et territoire, un rendez-vous manqué ? Le cas de Mayotte - Anne Cadoret (Éditions en environnement VertigO, 2016)
The Mayotte Marine Nature Park was established in January 2010, after a very rapid process. Responding to an environmental general interest, how did this national level initiative take root in the territory, based on the construction of a territorial sustainable development project and the territorialisation of the general interest driving the project? What is the basis of the social acceptability of the project? The analysis of the project construction process and controversies highlighted by stakeholders allow identifying biases and weaknesses in the construction of a territorialised general interest. The analysis focuses on the founding transactions of project acceptance, the differential of project ownership depending on the players, prioritisation of stakeholders and issues, the bias of representation on the "Sea parliament" that is the Park Management Board, the issues and the effectiveness of the construction of new organised proximities around the Park. We draw methodological lessons from this for the adequacy of the analysis grid used and subsequently operational experience on the means to implement for consultation, to target interfaces and fractures among actors rooted in distinct worlds.